2022
DOI: 10.3389/feart.2022.999593
|View full text |Cite
|
Sign up to set email alerts
|

Swabian MOSES 2021: An interdisciplinary field campaign for investigating convective storms and their event chains

Abstract: The Neckar Valley and the Swabian Jura in southwest Germany comprise a hotspot for severe convective storms, causing tens of millions of euros in damage each year. Possible reasons for the high frequency of thunderstorms and the associated event chain across compartments were investigated in detail during the hydro-meteorological field campaign Swabian MOSES carried out between May and September 2021. Researchers from various disciplines established more than 25 temporary ground-based stations equipped with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…This strategy not only increases the probability of encountering the desired weather extremes, but also releases synergies in the use of equipment, personnel, and scientific knowledge gain. As the follow-up campaign scheduled for 2020 in the Mueglitz catchment fell victim to the COVID-19 pandemic, the insights gained with this first test campaign were incorporated into the Swabian MOSES campaign of 2021 (Glaser et al 2022;Kunz et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy not only increases the probability of encountering the desired weather extremes, but also releases synergies in the use of equipment, personnel, and scientific knowledge gain. As the follow-up campaign scheduled for 2020 in the Mueglitz catchment fell victim to the COVID-19 pandemic, the insights gained with this first test campaign were incorporated into the Swabian MOSES campaign of 2021 (Glaser et al 2022;Kunz et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The field campaign Swabian MOSES was dedicated to hydro-meteorological measurements and was conducted by five Helmholtz research centres, three universities, and the DWD between May and September 2021 under the coordination of the Karlsruhe Institute of Technology (Kunz et al, 2022). The focus was on two hydro-meteorological extremes: (a) convective storms associated with heavy rainfall and hail, and (b) large-scale heat waves and associated droughts.…”
Section: 1mentioning
confidence: 99%
“…Recent studies have also shown that different assumptions for the amount of CCNs are relevant for quantitative precipitation forecasting and could be included in convective-scale ensemble prediction systems (Barthlott et al, 2022b;Baur et al, 2022;Keil et al, 2019;Matsunobu et al, 2022;Schneider et al, 2019). During summer 2021, the Swabian Modular Observation Solutions for Earth Systems (MOSES) field campaign was conducted in southwestern Germany (Kunz et al, 2022). On June 23, 2021, a supercell initiated in the southern Black Forest and passed directly over several observational sites.…”
Section: Introductionmentioning
confidence: 99%
“…Interested external partners can benefit from our sensor synergy and join through collaboration. For example, LAFO was one observation site in the frame of the field campaign Swabian MOSES that took place in spring 2021 (Kunz et al, 2022). During this field experiment the Atmospheric Raman Temperature and Humidity Sounder (ARTHUS) was operated to capture atmospheric temperature and humidity profiles next to wind and cloud observations with DL and a Doppler cloud radar.…”
Section: Sensor Synergymentioning
confidence: 99%